Toxicity of Bevacizumab in Combination with Chemotherapy in Older Patients. (10th April 2013) - Mohile, Supriya G.; Hardt, Molly; Tew, William; Owusu, Cynthia; Klepin, Heidi; Gross, Cary; Gajra, Ajeet; Lichtman, Stuart M.; Feng, Tao; Togawa, Kayo; Ramani, Rupal; Katheria, Vani; et al.
Abstract : Learning Objectives: Compare characteristics of older patients that receive bevacizumab plus chemotherapy to those treated with chemotherapy alone for advanced NSCLC and CRC. Compare outcomes between older patients treated with bevacizumab plus chemotherapy to chemotherapy alone for advanced NSCLC and CRC. Describe toxicities in older patients treated with bevacizumab plus chemotherapy for advanced NSCLC and CRC. Background: Bevacizumab leads to improved survival for patients with metastatic colorectal cancer (CRC) or non‐small cell lung cancer (NSCLC) when added to chemotherapy. Little is known about factors associated with receipt of bevacizumab, or whether bevacizamab is associated with increased toxicity when added to chemotherapy. Patients and Methods: We conducted a prospective study of patients aged ≥65 years, which evaluated the association between geriatric assessment (GA) metrics and chemotherapy toxicity. We examined differences in characteristics and outcomes of patients with CRC and NSCLC cancers who received bevacizumab with chemotherapy versus chemotherapy alone. Results: From a total of 207 patients, 27 (13%) received bevacizumab plus chemotherapy and 180 (87%) received chemotherapy alone. Groups were similar in sociodemographic and cancer characteristics. There were no baseline differences in GA domains except that patients with heart disease were less likely to receive bevacizumab (4% vs. 26%, p = .01). Seventy‐eight percent of patients who had bevacizumab had grade 3–5 toxicity compared to only 57% who received chemotherapy alone ( p = .06). Patients receiving bevacizumab were more likely to develop grade 3 hypertension than those who received chemotherapy alone (15% vs. 2%, p < .01). In multivariable analysis, factors associated with grade 3 or more toxicity included: bevacizumab (OR: 2.86, p = .04), CRC (OR: 2.54, p < .01), and baseline anemia (OR: 2.58, p = .03). Conclusion: Heart disease was more common in those who did not receive bevacizumab. Older patients who receive bevacizumab with chemotherapy have a higher odds of developing a grade 3–5 toxicity compared with those who receive chemotherapy alone. Abstract : Heart disease is more common in those who do not receive bevacizumab. Older patients who receive bevacizumab with chemotherapy have higher odds of developing a grade 3–5 toxicity compared with those who receive chemotherapy alone.